Bài 1: Chứng minh rằng:
a) [tex]8^{7}-2^{18}[/tex] chia hết cho 14
b) [tex]5^{5}-5^{4}+5^{3}[/tex] chia hết cho 7
c) [tex]7^{6}+7^{5}-7^{4}[/tex] chia hết cho 11
a) [tex]8^{7}-2^{18}[/tex] = [tex]2^21 - 2^18[/tex] = [tex]2^18 ( 2^3 - 1)[/tex] = [tex]2^18 . 7[/tex] = [tex]2^ 17 . 14[/tex] => [tex]8^{7}-2^{18}[/tex] chia hết cho 14
b) [tex]5^{5}-5^{4}+5^{3}[/tex] = [tex]5^3 ( 5^2 -5 +1)[/tex] = [tex]5^3. 21 [/tex]
mà 21 chia hết cho 7 nên suy ra [tex]5^{5}-5^{4}+5^{3}[/tex] chia hết cho 7
c) [tex]7^{6}+7^{5}-7^{4}[/tex] = [tex]7^4(7^2 + 7 - 1)[/tex] = [tex]7^4 . 55 = [tex]7^4 . 5 . 11[/tex] => [tex]7^{6}+7^{5}-7^{4}[/tex] chia hết cho 11[/tex]